Mosquito Larval Surveillance in a Rice Field in Tanjung Karang, Selangor, Malaysia - Wan-Norafikah, Othman; Chen, Chee Dhang; Mohd-Amir, Mohd Hanafie; Azahari, Abdul Hadi; Zainal-Abidin, Abu Hasan; Nazni, Wasi Ahmad; Mariam, Mariam; Mohd-Shahizan, Jamil; Sofian-Azirun, Mohd (American Scientific Publishers, 2017)
Mosquito larval surveillance was carried out in a rice field in Tanjung Karang, Selangor, Malaysia to determine the diversity of breeding habitats of mosquito larvae and species composition of those mosquito larvae that bred in positive habitats within the study area. From 215 potential mosquito breeding habitats inspected, 93.90% outdoor containers and 6.10% indoor containers were positive with mosquito breeding. Artificial containers (71.95%) were favorable breeding habitats of mosquito larvae compared to natural containers (28.05%). Only Aedes albopictus Skuse (80.80%) and Culex quinquefasciatus Say (19.20%) larvae were collected from all positive breeding habitats. This result shows that Ae. albopictus is a predominant outdoor breeder in the study area and could also invade indoors. It is crucial to identify the mosquito species available in the study area and their habitats to ensure the effectiveness of vector control strategies conducted so that the transmission of any mosquito-borne diseases could be avoided or lessened.